Angus, thongs and full-frontal snogging : confessions of Georgia Nicolson - Rennison, Louise (New York : HarperTempest, 2000)
Presents the humorous journal of a year in the life of a fourteen-year-old British girl who tries to reduce the size of her nose, stop her mad cat from terrorizing the neighborhood animals, and win the love of handsome hunk Robbie.
Sequel: On the bright side, I'm now the girlfriend of a sex god.
700
700
Accelerated Reader AR
Keywords: Diaries -- Juvenile fiction; Humorous stories; England -- Juvenile fiction